Adsorptive removal of multi-azo dye from aqueous phase using a semi-IPN superabsorbent chitosan-starch hydrogel - Ngwabebhoh, Fahanwi Asabuwa; Gazi, Mustafa; Oladipo, Akeem Adeyemi (Elsevier, 2016)
This article reports the efficient removal of Direct Red 80 (DR80) dye from aqueous phase using a semi-interpenetrating network (IPN) superabsorbent chitosan-starch (ChS) hydrogel. In the present investigation, the influence of initial pH, ChS dose, initial dye concentration, temperature and effect of salts on the sorption of DR80 dye was evaluated. A maximum swelling capacity of 15 g/g was determined for ChS hydrogel. The sorption equilibrium data demonstrated good agreement with Freundlich isotherm. The sorption process best fitted the pseudo-second order kinetic model. Maximum uptake capacity of the hydrogel was determined as 312.77 mg/g. The mean sorption energy (E = 11.34-14.9 kJ/mol) demonstrated that DR80 sorption was mainly chemisorption. The temperature dependence data revealed the sorption process was spontaneous, endothermic and favourable at higher temperature based on the enthalpy (Delta H degrees = +83.68 kJ/mol) value obtained. Boyd model confirmed intra-particle diffusion was the limiting step for DR80 uptake. In addition, sorption/desorption studies were performed to investigate the reusability of ChS hydrogel which demonstrated significant sorption for four consecutive cycles. (C) 2016 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Semi-interpenetrating; Superabsorbent; Hydrogel; Chitosan-Starch; Direct Red 80